THE USE OF E-WALLETS DURING THE COVID-19 PANDEMIC ON MSMES IN DEPOK CITY - Pusporini Pusporini; Bernadin Bernadin; Yudi Nur Supriadi (SEAN Institute, 2022)
The development of technology in Indonesia is becoming more sophisticated and modern. One of them is the smartphone, whose use is getting more sophisticated. Besides being a means of communication, smartphones are now a new means of payment transactions or mobile payments. Therefore, mobile payment systems such as e-wallets are growing in facilitating online or offline transactions using only QR codes. This study aims to determine performance expectations, effort expectations, social influence, perceived risk, and perceived costs toward behavioral intentions for E-Wallet users in Depok City. The method used in this study is a descriptive method with a quantitative approach and uses a hypothesis testing technique, namely the T-test. Based on the results of data processing using SmartPLS, obtained Effort Expectation, Social Influence, and Perceived Cost significantly affects the Behavior Intention of E-Wallet Users in MSMEs in Depok City. However, Performance Expectations and Perceived Risk did not significantly affect the Behavior Intention of E-Wallet Users in MSMEs in Depok City. However, Performance Expectations and Perceived Risk did not significantly affect the Behavior Intention of E-Wallet Users in MSMEs in Depok City